The Political and Structural Exclusion of Student Voice in the School Closure Process - Toneff-Cotner, Glenda (In Factis Pax: Journal of Peace Education and Social Justice, 2015)
School Closure in the United States is steeped in educational policy and has historically been associated with declining student enrollment, limited financial resources, and consolidation of schools and/or districts (Tyak, 1974). Since the early 1980’s, an increase in neoliberal and neoconservative ideology reflecting market-driven reforms has resulted in educational policy grounded in standards-based curriculum, high-stakes testing and school choice.